Axon-specific microtubule regulation drives asymmetric regeneration of sensory neuron axons - Ana Catarina Costa; Blanca R Murillo; Rita Bessa; Ricardo Ribeiro; Tiago Ferreira da Silva; Patrícia Porfírio-Rodrigues; Gabriel G Martins; Pedro Brites; Matthias Kneussel; Thomas Misgeld; Monika S Brill; Monica M Sousa (eLife)
Sensory dorsal root ganglion (DRG) neurons have a unique pseudo-unipolar morphology in which a stem axon bifurcates into a peripheral and a central axon, with different regenerative abilities. Whereas peripheral DRG axons regenerate, central axons are unable to regrow. Central axon regeneration can however be elicited by a prior conditioning lesion to the peripheral axon. How DRG axon asymmetry is established remains unknown. Here we developed a rodent in vitro system replicating DRG pseudo-unipolarization and asymmetric axon regeneration. Using this model, we observed that from early development, central DRG axons have a higher density of growing microtubules. This asymmetry was also present in vivo and was abolished by a conditioning lesion that decreased microtubule polymerization of central DRG axons. An axon-specific microtubule-associated protein (MAP) signature, including the severases spastin and katanin and the microtubule regulators CRMP5 and tau, was found and shown to adapt upon conditioning lesion. Supporting its significance, interfering with the DRG MAP signature either in vitro or in vivo readily abolished central-peripheral asymmetries in microtubule dynamics and regenerative ability. In summary, our data unveil that axon-specific microtubule regulation drives asymmetric regeneration of sensory neuron axons.